Readings from the ancient near east primary sources for Old Testament study - Beyer, Bryan E.; Arnold, Bill T. 1955- (Grand Rapids, MI Baker Academic, 2002)
Includes bibliographical references andindexes.
Keywords: Middle East -- Religion -- History -- Sources; Bible. O.T. -- history of contemporary events -- sources